Analisis Sun Hours Dalam Desain Bangunan Tropis Menggunakan Simulasi 3D: Studi Kasus Pada Periode Ekuinoks dan Solstis - Mustakima, Dui Buana; Nike, Nike; Cahyani, Cahyani; Hikmah, Nurul; Nugroho, Isti (Jurusan Teknik Arsitektur, Fakultas Teknik Universitas Tadulako Kampus Bumi Tadulako Tondo Jl. Sukarno-Hatta Km.9, Palu 94118 e-mail :Jurusan Arsitektur, Fakultas Teknik Universitas Tadulako Kampus Bumi Tadulako Tondo Jl. Sukarno-Hatta Km.9, Palu 941, 2025)
Thermally comfortable tropical building designs must respond to sunlight exposure. Detailed data on the duration of sunlight exposure during the equinox and solstice periods is still limited. This study aims to analyze sunlight exposure during the equinox and solstice periods. The research was conducted using the Forma application, a 3D simulation product. The results show that the roof receives the highest sunlight exposure, reaching 9 hours per day during the equinox, while some areas of the building facade only receive exposure for less than 1 hour per day during the solstice. These findings provide important insights into the optimization of shading design and energy efficiency in tropical buildings. This research has a positive impact on architectural knowledge, demonstrating that simulation-based design can be used in creating sustainable tropical buildings